Peran Guru Ilmu Pengetahuan Sosial (IPS) dalam Meningkatkan Kemampuan Berpikir Kritis Siswa Kelas 8 pada Era Digital di SMPN 1 Boyolangu - Ajeng Arina Manasikana; Hendra Pratama (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Critical thinking skills are essential for every student, especially in today's digital era, where information is spread so freely and without limits. Students need to be taught how to think critically to make the right decisions regarding the information obtained. At school, developing critical thinking skills will help students face increasingly complex challenges. In this case, teachers play a very important role in guiding and educating students to develop these skills well. The objectives of this study are: 1) To find out the role of social studies teachers in improving the critical thinking skills of 8th grade students in the digital era of Ngeri 1 Boyolangu Junior High School. 2) To find out the steps used by social studies teachers to develop critical thinking skills of 8th grade students at Ngeri 1 Boyolangu Junior High School. 3) To find out the inhibiting and supporting factors in developing students' critical thinking skills. The approach used in this research is qualitative. data collection procedures in this study using observation, interviews and documentation. Data analysis techniques are carried out through data collection, data reduction, data display, and data verification. Research Results: 1) Teachers play a role in designing lesson plans with varied learning methods, in each method there are discussion activities, teaching by taking real problems in accordance with the reality related to the material in the classroom, familiarizing students to ask, answer, provide input and provide simple solutions related to the problems given.2) Steps to Develop Students' Critical Thinking Skills, including teachers getting students used to asking questions, answering, providing simple solutions related to the problems given. Teachers use digital media, such as PowerPoint and websites, as well as game-based learning, which not only makes learning more interesting but also supports students' critical thinking skills through technology. Teachers provide positive motivation to encourage students to participate more actively in learning. 3) The inhibiting factors include the rapid flow of digital information, “filter bubble,” lack of digital literacy, and low learning independence. Supporting factors include motivation from teachers or parents and students' intellectual development, which encourages exploration of information and a higher learning spirit.